2018
DOI: 10.4018/ijsesd.2018070102
|View full text |Cite
|
Sign up to set email alerts
|

A Business Model Framework for Crowd-Driven IoT Ecosystems

Abstract: This article describes how the era of hyper-connectivity is characterized by distributed, crowd-centric ecosystems that utilise cutting edge technology so as to harness the collective power, co-creation ability and intelligence of the crowd utilising under open participatory value creation models. The Internet of Things (IoT) has fueled the emergence of such ecosystems that leverage not only the power of physical things connected to the Internet but also the wisdom of the crowd to observe, measure, and make se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…, 2021). By introducing cutting-edge technology such as artificial intelligence (AI) and BCT into the mHealth care system, I4.0 principles can link the virtual network with the actual environment; this also addresses the various barriers related to intellectual technologies (Ziouvelou and McGroarty, 2018). Kamble et al .…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2021). By introducing cutting-edge technology such as artificial intelligence (AI) and BCT into the mHealth care system, I4.0 principles can link the virtual network with the actual environment; this also addresses the various barriers related to intellectual technologies (Ziouvelou and McGroarty, 2018). Kamble et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Industry 4.0 was established through the application of contemporary information technologies, including cyber-physical systems, the Internet of things and data analytics (big data) (Madanian et al, 2019a(Madanian et al, , 2019bSimeone et al, 2021). By introducing cutting-edge technology such as artificial ISM analysis of barriers of mHealth adoption intelligence (AI) and BCT into the mHealth care system, I4.0 principles can link the virtual network with the actual environment; this also addresses the various barriers related to intellectual technologies (Ziouvelou and McGroarty, 2018). Kamble et al identified twelve challenges to the adoption of Industry 4.0 in various manufacturing sectors in 2018.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation